IMPROVING THE METHODS OF STRENGTHENING THE ROLLING STOCK AND MEASURES TO PREVENT ACCIDENTS IN THE EVENT OF THEIR SPONTANEOUS DEPARTURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Currently, one of the main issues in ensuring the safety of train traffic at Uzbekistan Railways is the reliable fastening of trains to prevent them from leaving the station as a result of spontaneous movement of trains. The scientific article outlines the principles of ensuring the safety of rolling stock currently available on station tracks and the use of methods to prevent other trains from exiting the tracks in the event of a spontaneous departure of rolling stock.In addition, the methods of strengthening the rolling stock of the railways of the CIS and foreign countries, as well as the prevention of spontaneous departure of trains, were analyzed, and suggestions were made that could improve the performance of the railway station.